Serum tumor markers and their prognostic value in Turkish hepatocellular cancer patients - Lacin, Sahin; Yalcin, Suayib (Annals of Medical Research, 2021)
Aim: Association between serum tumor markers and hepatocellular cancer (HCC) patients’ survival has been investigating for decades. Despite glypican 3 has been reported superior to AFP in predicting the prognosis of HCC patients recently, the prognostic value of glypican 3 not clear. We aimed to investigate the prognostic value of serum glypican 3 and its relationship with the characteristic features in the Turkish HCC patients’ cohort.Material and Methods: A total of 84 HCC patients were enrolled prospectively. Serum glypican 3 levels were analyzed and serum levels of glypican 3 were compared according to many different types of the clinicopathologic features of HCC.Results: A total of 84 patients, 71 of the patients were male and 13 were female. There were 36 hepatitis B (HBV) and 8 hepatitis C (HCV) infected patients. Forty-eight patients had cirrhosis and 35 patients did not. Serum glypican 3 levels were lower in cirrhotic than non-cirrhotic patients (p =0.6). Difference between overall survival (OS) of patients with serum glypican 3 levels ≥ 2 ng/mL and patient with serum glypican 3 level 2 ng/mL was not significant, the OS estimates were 7.8 and 6.1 months, respectively (p=0.3). The median OS was 7.38 months. There was a positive correlation between serum AFP level and glypican 3, but not statistically significant (p=0.07). Conclusion: The study results indicate that serum glypican 3 level is elevated in HCC patients with poorer features. Therefore, despite nonsignificant results, the method that contains the prediction of HCC patients’ survival by serum glypican 3 level needs to be clarified with larger trials.